Comparative effectiveness of a pilot patient-centered ultrasound report in the management of hydronephrosis. Issue 1 (February 2018) - Dy, Geolani W.; Gore, John L.; Muncey, Wade W.; Ellison, Jonathan S.; Merguerian, Paul A.
Summary: Purpose: Hydronephrosis is a common pediatric abnormality and can be associated with substantial parental anxiety, especially in the prenatal period. Radiology reports contain complex content that can be difficult for lay audiences to comprehend, potentially contributing to parental distress. Materials and methods: We developed and piloted a patient-centered radiology report (PCRR) for renal ultrasounds (US) in children with hydronephrosis (Figure). We obtained consensus from a multidisciplinary panel of experts regarding critical US report components. A parent focus group provided input regarding syntax and formatting of a PCRR, incorporating elements deemed valuable by the expert panel. We prospectively recruited parents of children who underwent US for hydronephrosis and randomized parents to receive either the PCRR + standard report (SR) or SR alone. Web-based surveys assessed self-efficacy and knowledge of US elements. Results: Our pilot study included 20 SR patients and 24 PCRR patients, with no difference in demographic or disease characteristics between groups. Self-efficacy scores were uniformly high in both groups ( p  = 0.79). PCRR parents trended towards increased accuracy in identifying presence of severity (88% vs. 70%; p  = 0.15) and bilaterality (67% vs. 45%; p  = 0.15), with minimal difference in identifying parenchymal pathology (75% vs. 70%; p  = 0.71) and bladder abnormalities (88% vs. 85%; p  = 0.81). Parents were more confident in their ability to understand the PCRR (92% vs. 60%; p  = 0.01). Conclusions: A PCRR was associated with significantly higher confidence in US report interpretation, but was underpowered to demonstrate increased accuracy in identifying US findings. These findings justify future studies of PCRRs for hydronephrosis care. Figure Study methods.